Indoor air quality and respiratory health implication among Malay preschool children in Puchong and Hulu Langat Selangor, Malaysia - Onwusereaka, Cynthia Oluchi; Jalaludin, Juliana; Hisamuddin, Nur Hazirah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Indoor air pollutant has caused a greater impact on the health of occupants’ especially preschool age who are still growing. Objective: To determine the association between indoor air pollutants (Particulate Matter (PM2.5, PM10), Volatile Organic Compounds (VOCs), mould) and respiratory implications among preschool children in Selangor. Methods: A cross-sectional comparative study was conducted on 270 preschool children in Puchong (study area) and Hulu Langat (comparative area). Respiratory symptoms were assessed using a questionnaire adapted from the American Thoracic Society (ATS). DustTrak Aerosol monitor was used to assess PM2.5 and PM10; PbbRAE for measuring VOCs; Q-Trak Monitor for temperature and relative humidity; VelociCalc for air velocity; Pbi DuoSAS Super 360 for mould; Chestgraph HI-101 spirometer for lung function test (Forced Expiratory Volume in 1 second/Forced Vital Capacity (FEV1/FVC%) and FEV1%. Results: Indoor PM2.5, PM10 and mould in the study area was significantly higher (p=0.001). There was a significant difference in FEV1/FVC%, and FEV1% predicted in the study and comparative group (p<0.05). There was a significant association between PM2.5 and PM10 with cough (p<0.005). Indoor PM10 and VOCs were significantly associated with FVC% (p<0.05). VOCs was significantly associated with FEV1% (p<0.001). Logistics regression analysis showed that the risk of FEV1% abnormality increased significantly with increase in PM10 (OR=2.1, 95% CI=2.509-8.221), VOCs (OR=5.3, 95% CI=1.912-14.835) and RH (OR=14.3,95% CI= 1.451-14.306). Conclusion: High exposure to indoor air pollutants increases respiratory symptoms and reduce lung function among children. The moisture-damaged building materials need to be replaced to avoid mould growth.